2017
DOI: 10.15761/cogrm.1000203
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar lichen sclerosus: could a moisturizing and healing product reduce the prolonged use of topical steroid?

Abstract: Background: Vulvar lichen sclerosus (LS) is an immune-mediated disease of unknown etiology causing itch, burning, and plaques with overlying excoriation and linear fissures. The standard treatment for this disease is the use of topical corticosteroids but evidence on the most appropriate treatment regimen is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Borghi et al (2015) obtained 52.4% and 28.6%, respectively, according to their global score (5 of our 9 criteria: erythema, leukoderma (pallor), sclerosus/scarring/atrophy, hyperkeratosis, and purpura/erosion). Murina et al (2017) used a global severity score (0-3) and also found a statistically significant decrease in vulvar signs. Fissures and erosions were the two clinical signs that showed the most improvement across both groups of patients in D'antuono et al 's study (2011).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Borghi et al (2015) obtained 52.4% and 28.6%, respectively, according to their global score (5 of our 9 criteria: erythema, leukoderma (pallor), sclerosus/scarring/atrophy, hyperkeratosis, and purpura/erosion). Murina et al (2017) used a global severity score (0-3) and also found a statistically significant decrease in vulvar signs. Fissures and erosions were the two clinical signs that showed the most improvement across both groups of patients in D'antuono et al 's study (2011).…”
Section: Discussionmentioning
confidence: 98%
“…The difference may be explained by the TS maintenance therapy used in our study population. Murina et al (2017) studied soft foam use for the supportive treatment of LS (n = 43). Twenty-one patients were treated with MMF 0.1% for 4 weeks; then, twice weekly for 4 weeks in combination with a moisturizing cream; 22 patients were treated with MMF for 20 days, then with a soft foam.…”
Section: Discussionmentioning
confidence: 99%